Mechanical Effects of Wrist Position at the Wrist Joint: A Finite Element Analysis - Takashi Nomoto, MD; Yusuke Matsuura, PhD; Takahiro Yamazaki, PhD; Takane Suzuki, PhD; Seiji Ohtori, PhD (Journal of Hand Surgery Global Online)
Purpose: This study aimed to evaluate the effects of wrist joint angles during flexion–extension and radioulnar deviation on stress distribution using finite element analysis. Methods: Eight fresh-frozen upper limb specimens were analyzed using computed tomography. Finite element models were developed to simulate grip postures in flexion–extension (five positions ranging from 30° flexion to 30° extension) and radioulnar deviation (eight positions from 15° radial deviation to 20° ulnar deviation). Stress distributions (equivalent stress, minimum principal stress, and maximum principal stress) in the distal radius, ulnar head, and proximal carpal bones were assessed. Results: In the flexion–extension model, stress was concentrated in the central area of the distal radius and increased with an increase in flexion–extension angles. Stress values in the ulnar head and triquetrum increased during flexion and extension, whereas stress changes were minimal in the scaphoid and lunate. The scaphoid fossa experienced higher stress than the lunate fossa, with the volar aspect of the distal radius under greater stress during extension and the dorsal aspect during flexion. In the radioulnar deviation model, radial deviation decreased the load on the lunate fossa while increasing the load on the ulnar head, triquetrum, and dorsal lunate. Conversely, ulnar deviation reduced the load on the ulnar head but increased the load on the volar aspect of the lunate fossa. Conclusions: Finite element analysis demonstrated dynamic changes in wrist joint stress distribution at various motion angles. Clinical relevance: These findings enhance the understanding of wrist biomechanics and provide insights into the pathomechanics of degenerative wrist conditions.